Value component in the structure of the motivational sphere of a serviceman's personality - HULIAK, Uliana; LISNEVSKYI, Vladlen (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
B a c k g r o u n d . The article presents an analysis of modern theories and studies of the motivational sphere of personality, its structure, psychological features of functioning, and, in particular, in the context of combat activity, with the aim of outlining the value component in the structure of the motivational sphere of a serviceman's personality, defining it, and clarifying how values influence the motivation of a serviceman to combat activity.M e t h o d s . To solve the tasks set in this paper, theoretical research methods were used: analysis of scientific sources on the research topic, system analysis, synthesis, generalisation of scientific approaches, classification and specification of the system of values that determine the combat motivation of military personnel.R e s u l t s . The results indicate the key role of values in shaping the motivation of servicemen to fight, perform daily combat tasks and the desire to return to the battlefield. The analysis of scientific works shows that the motivational and value sphere is unique for each individual and a complex structure that inspires a person, encourages and gives strength to overcome life՚s difficulties. The analysed studies have also made it possible to state that the motivational and value sphere of personality as an integral psychological formation is currently represented through the phenomena of the value-sense sphere, personal values, goals of life, personal, social, and professional significance. In order to determine the motivational and value determinants of military personnel's combat activity, the characteristic features of such activity are analysed. The key definitions reflecting the relationship between values and motivation and their influence on the activity of the serviceman's personality in combat conditions are formulated.С o n c l u s i o n s . The motivational and value sphere enables the serviceman՚s personality to compare his own needs and motives with the values and social norms he has learned and understood, and regulates his activity. At the same time, it not only determines the ways and conditions for achieving goals, but also becomes a source of goals. In addition, the motivational and value sphere reflects the subjective attitude of a serviceman՚s personality to social reality, which manifests itself as a motivation for combat activity, behaviour in different situations and spheres of life. In the structure of a serviceman's personality, the motivational and value sphere characterises the internal readiness for combat activity and determines the direction of behavioural activity.
Keywords: motivation; values; motives; meaning; motivational and value sphere; combat activity; military personnel